2018
DOI: 10.30598/jbkt.v2i1.235
|View full text |Cite
|
Sign up to set email alerts
|

Bimbingan Kelompok dengan Teknik Sosiodrama Sebagai Upaya Mengatasi Perilaku Bullying di Sekolah

Abstract: Bullying behavior is a behavior that many found among people in recent times. Many argue that bullying behaviors include behaviors that aim to intimidate others, discredit others, and even injure others. Different forms of bullying behaviors, some of which include bullying, threatening, mocking, calling offensive calls, and isolating or alienating others in a group. There are many impacts of bullying behavior, including individuals who become inferior, depressed, depressed, or even selfrebellious and revengefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
3
0
7
Order By: Relevance
“…Some conditions that must be fought in this case are the irrational beliefs and assumptions of the counselee as previously described, including feelings of satisfaction and pleasure over the verbal bullying behavior. The guidance and counselling services are carried out using a group guidance for 3 (three) meetings, where each meeting is held in the auditorium during active learning hours for approximately 45 minutes (Adit et al, 2019;Kurniawan & Pranowo, 2018). This is carried out by arranging chairs in a circle, which aims to make it easier for counsellors, counselees and observers to interact during the service (Muhammad & Machali, 2016;Sumarni, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some conditions that must be fought in this case are the irrational beliefs and assumptions of the counselee as previously described, including feelings of satisfaction and pleasure over the verbal bullying behavior. The guidance and counselling services are carried out using a group guidance for 3 (three) meetings, where each meeting is held in the auditorium during active learning hours for approximately 45 minutes (Adit et al, 2019;Kurniawan & Pranowo, 2018). This is carried out by arranging chairs in a circle, which aims to make it easier for counsellors, counselees and observers to interact during the service (Muhammad & Machali, 2016;Sumarni, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, by giving guidance and counselling services that are specifically held to prevent, handle or reduce verbal bullying behavior. The results of previous studies indicated that group guidance services are one of the service that can be applied in dealing with bullying behavior (Adit et al, 2019;Kurniawan & Pranowo, 2018;Rizki et al, 2019;Saputri & Zuhdi, 2022;Simarmata & Muhazir, 2021). Group guidance is carried out according to the students' need who are selected to be involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying berasal dari kata bully merupakan suatu kata yang merujuk kepada adanya suatu bentuk "ancaman" yang dilakukan oleh seseorang terhadap orang lain yang umumnya lebih lemah atau "rendah" dari perilaku, yang dapat menimbulkan gangguan psikologis maupun fisik pada korban (korban disebut bully atau bully girl) berupa stress (yang muncul dalam bentuk gangguan fisik atau psikis, atau keduanya; misalnya susah makan, sakit fisik, ketakutan, rendah diri, depresi, cemas dan lainnya (Kurniawan & Pranowo, 2018). Menurut PEKA (Peduli Karakter Anak) adalah penggunaan agresi dengan tujuan untuk menyakiti orang lain baik secara fisik maupun secara mental.…”
Section: Pendahuluanunclassified
“…Bullying tidak hanya tentang tindakan yang dilakukan, tetapi juga dampak yang ditimbulkan atas tindakan tersebut bagi korban. (Kurniawan & Pranowo, 2018). Kellerman (2007) (Marineau, 1989;Kellerman, 2007).…”
unclassified